Motor imagery and rehabilitation of a professional soccer player after anterior cruciate ligament injury: a case report - Mangone, M.; Bernetti, A.; Paolini, M.; Canonico, R.; Tognolo, L.; Attanasi, C.; Cruciani, A.; Alvitti, F.; Santilli, V.; de Nicola, A. (Medicina dello Sport, 2017)
Anterior cruciate ligament (ACL) injury is one of the most common musculoskeletal injuries; it is the third most important injury in elite athletes after muscular strains and fractures. Generally, an early rehabilitation is needed in order to obtain an optimal restoration of both knee joint stability and sensory function. In the first part of the rehabilitation phase, when the athlete cannot get the job done in the field yet, it can be useful to perform the action observation (AO) and motor imagery (MI) training. This is a case report about a 24-year-old professional soccer player who reported an ACL injury and medial collateral ligament (MCL) during a league game. During the rehabilitation period, the player has remained in close contact with his teammates, staying on the field right away during workouts, without participating actively. The technique of "motor imagery" and action observation were applied to reinforce the effect of rehabilitation and reduce recovery times. The follow-up consisted in a muscle strength evaluation with an isokinetic test and a postural assessment using a video-raster-stereography system "Formetric". At the end of the rehabilitation program, the player returned to the activity in less time than normal recovery time as described in literature.